Geographical Information Systems as Learning Resources for Social Studies: A Literature Review - Onamrewho Favour Atubi; Peter Ogbianugene Dania (MO.RI Publishing, 2022)
The use of innovative and advance resources like those of Geographical Information Systems (GIS) to for Social Studies can aid the actualization of the aims and objectives of Social Studies education in Nigeria. This theoretical paper pointed out the fact that Geographical Information Systems can be used to achieve quality Social Studies education in Nigeria through exploring available literature to provide a good understanding of the topic under review. The paper adopted an analytical approach through extensive review of literature around the major variables which are Geographical Information Systems and Social Studies. It further discussed the relationship between Social Studies and Geographical Information Systems as well as the benefits which will be accrued to both learners and educators of Social Studies by using them as instructional references for Social Studies lessons. The paper concluded by explaining the benefits of applying Geographical Information Systems resources to Social Studies. These benefits include providing students with visual learning of Social Studies; studying the major themes of Social Studies through a spatial perspective; using stored information for education and applying technology to educational processes as it concerns learning in Social Studies.